Association Between Child Maltreatment and Aggression in Chinese Early Adolescents: The Mediating Role of Irritability - Xu, Baoyu (Journal of interpersonal violence, 2024)
Child maltreatment (CM) is a major global public health issue, and a strong association exists between CM and aggression. However, the underlying mechanism of this association has not been understood to date. The objective of this study was to explore the mediating role of irritability in the association between CM and aggression in Chinese early adolescents. A cross-sectional study was conducted using a self-report questionnaire to evaluate the levels of CM, aggression, and irritability in 5,724 middle school students from the Anhui Province, China. Structural equation modeling was used to test the hypothesis of the mediating effect of irritability on the relationship between CM and aggression. We further investigated gender differences in this association using multiple group analyses. CM was positively related to both irritability and aggression, and irritability was positively associated with aggression (p < .01). The mediating effects of irritability between CM and aggression were significant (β = .107, 95% confidence intervals [CI]: 0.077–0.133, p < .05). Males had a higher indirect effect size of the pathway from CM to aggression via irritability compared with females. Overall, irritability was a crucial mediator in the relationship between CM and aggression in Chinese adolescents, and males were more prone to engage in aggression compared with females through the pathway of irritability. Therefore, early irritability characteristics should be carefully monitored in adolescents, and they should be provided adequate support to acquire critical emotion regulation skills.